Analisis kesalahan menyelesaikan soal cerita pada materi keliling dan luas bangun datar berdasarkan newman’s error analysis ditinjau dari gaya kognitif peserta didik kelas IV sekolah dasar - Indar Diasmi Aulianisa; Riyadi Riyadi; Muhammad Ismail Sriyanto (Didaktika Dwija Indria, 2022)
This study aims to find out the errors in solving the story questions about the circumference and area of flat shapes based on Newman Error Analysis in fourth grade students of SD Negeri Joho 01 Sukoharjo District in terms of field dependent and field independent cognitive styles. This study uses a qualitative method with a case study approach. The subjects of this study consisted of 4 students. Research subjects were selected using purposive sampling. Research subjects were selected based on the results of the GEFT test. Data collection methods in this study were tests, interviews, and documents. The test given is 5 questions about the circumference and area of the plane. Data validation was carried out using triangulation techniques, namely comparing the data from the written test results with interviews that were equipped with documents from students. Data analysis used the Newman Error Analysis method. Based on the results of the analysis that has been carried out, it shows that the errors in solving story problems in students with field dependent tend to be the same as students with field independent cognitive style. There are 4 types of errors, namely comprehension errors, transformation errors, process skills errors, and encoding errors. The mistakes made by students with field dependent are more than students with field independent cognitive style.